Forests for Livelihood, Economic Security and Eradication of Poverty - Tewari, Dina Nath (Indian Forester, 2017)
Sustainable Development Goals were adopted encompassing universal aspirations centred on people, planet, peace and partnership with endeavour to achieve sustainability and leaving no one behind in the progress of development. Progress has bypassed groups, communities, societies and people have been left out and new challenges have emerged for ending poverty, hunger, inequality, climate change, conflicts and violent extremism. Increasingly perceptible resource depletion (deforestation and forest degradation) and climate change highlight the importance of integrating environmental sustainability into development strategies (such as ’green economy’, ’green growth’ and ’carbon’ neutral development’) for the good of present and future generations.